EU Cohesion Policy on the Ground: Analyzing Small-Scale Effects Using Satellite Data - Julia Bachtrögler-Unger; Mathias Dolls; Carla Krolage; Paul Schüle; Hannes Taubenböck; Matthias Weigand (Center for Economic Studies and ifo Institute (CESifo), 2022)
We present a novel approach for analyzing the effects of EU cohesion policy on local economic activity. For all municipalities in the border area of the Czech Republic, Germany and Poland, we collect project-level data on EU funding in the period between 2007 and 2013. Using night light emission data as a proxy for economic development, we show that the receipt of a higher amount of EU funding is associated with increased economic activity at the municipal level. Our paper demonstrates that remote sensing data can provide an effective way to model local economic development also in Europe, where no comprehensive cross-border data is available at such a spatially granular level.
Keywords: R11; O18; H54; 330; regional development; EU cohesion policy; remote sensing